"It's better than it used to be": Perspectives of adolescent siblings of children with an autism spectrum condition. Issue 4 (24th April 2017) - Gorjy, Rebecca Soraya; Fielding, Angela; Falkmer, Marita
Abstract : This article reports on the lived experiences of 11 adolescents who have a brother or a sister with a diagnosis of autism spectrum condition. Through semistructured, in‐depth, in‐person interviews, these adolescents shared their experiences and perceptions. These exploratory findings can be used to inform the practice of social workers and other health professionals, and future research. Implications for practice focus on the importance of exploring experiences and perceptions of siblings of children diagnosed with autism spectrum condition to enhance support services for these siblings.